Intestinal permeability of autistic and healthy children as measured by D-xylose test - Hardiono D Pusponegoro; Tuty Rahayu; Agus Firmansyah (Indonesian Pediatric Society, 2006)
Background The etiopathogenesis of autistic disorder is unknown.Some authors suggest that food peptides may reach the centralnervous system through a defect of intestinal permeability and pro-duce toxic effects resulting in behavior impairment.Objectives To investigate the prevalence of increased intestinalpermeability in children with autistic disorder using oral D-xylosetest.Method A cross-sectional study was conducted on 27 childrenwith autistic disorder and 54 healthy children (27 siblings and 27unrelated children matching with those of the autistic group). Thesubjects underwent oral D-xylose test. Subjects were free fromfever, drugs, and diarrhea. Student t-test and chi-square were usedfor statistical analysis.Results Prevalence of increased intestinal permeability in the au-tistic group was 63%, which proved to be significant (P=0.007,95%CI: -0.931; -0.987) compared to controls.Conclusion The intestinal permeability significantly increased inautistic children